Demand for money function in Ireland - estimation and stability - Browne, Francis X.; O'Connell, Thomas (Economic & Social Studies, 1978)
In this paper we specify and estimate a demand for money function for Ireland. This function is then submitted to a stability test using a recently developed technique. The issue of the stability of the demand for money function is an important one for the monetary authorities irrespective of whether monetary policy is conducted within a relatively closed economy, such as in the US, or within a highly open economy with a fixed exchange rate dominated by external financial markets, as in the case of Ireland.
Keywords: Monetary policy - Ireland; Fixed exchange rate